욕망과 깨달음: 역사를 움직이는 두 가지 힘 -불교의 역사관 시론 - 정천구; Jeong Chun-koo (한국교수불자연합학회지, 2019)
불교에는 서양의 역사관과 구별되는 역사관이 있는가? 있다면 어떤 것인가? 불교에서 역사란 무엇이라 보며, 역사의 주체는 누구라고 보는가? 불교에서 역사는 어떠한 방향으로 진행되고 있다고 보며 역사를 움직이는 힘을 무엇이라고 보는가? 이 글은 이런 문제들에 답하기 위하여 쓴 글이며 이를 위하여 계몽시대 이후 전개된 역사관, 그리고 이의 연장선상에서 냉전의 종식을 계기로 후쿠야마(Francis Fukuyama)에 의해 제기되었던 「역사의 종언」의 쟁점들을 검토하고 이를 계기로 불교의 역사관을 정립하기 위한 시론(試論)이다. 본론은 먼저 역사연구에 있어서 중요한 기초로 삼아야할 일은 역사적 사실이라고 본다. 역사에 관한 어떠한 연구도 역사적 사실을 기본으로 한다는 점에서 역사적 사실 자체를 부정하거나 현재의 시각에서 과거의 사실을 변경시키거나 왜곡하지 말아야 한다. 근대 이후 역사철학은 정신변증법에 기반을 둔 헤겔의 역사철학과 이를 유물변증법으로 바꾼 마르크스의 역사관으로 대별될 수 있다. 둘 다 역사의 시작과 종말이 있다는 점에서는 같다. 그러나 역사를 절대정신의 자유 실현과정으로 본 헤겔은 프랑스 혁명으로 자유. 평등의 이상을 국가원리로 채택했기 때문에 역사의 종언에 도달했다고 주장했고 마르크스는 자본가 계급을 타도하는 공산주의 혁명으로 역사의 종언에 이른다고 주장했다. 그러나 소련의 멸망과 사회주의권의 붕괴를 눈앞에 두고 프랜시스 후쿠야마는 공산주의의 멸망으로 자유민주주의가 최종 승리함으로써 역사는 종언이 왔다고 주장했다. 그는 마르크스주의자에서 헤겔주의자로 변신한 코제브의 이론을 이어받아 역사를 움직여온 힘을 「인정을 받기 위한 투쟁」으로 보았다. 여기에 자연과학의 발달로 경제적 발전을 위한 경쟁이 더해졌다. 그는 공산주의는 경제적 번영에 있어서도 자유민주주의를 이길 수 없었고 인정을 위한 투쟁에서도 보편적 인권을 지향하는 자유민주주의를 이길 수 없었다고 썼다. 그러나 향후 세계를 전망하는 논의에서 사무엘 헌팅턴은 20세기의 이데올로기의 투쟁은 「문명의 충돌」로 대체된다고 주장해서 후쿠야마의 「역사의 종언」과 맞섰다. 두 사람 간의 중요한 차이점의 하나는 과학기술문명이 보편적인 문명이냐 아니면 서구문명의 연장으로서 다른 문명들과 구별되는 문명의 발전이냐는 점이다. 또 공산주의의 멸망을 역사의 종언으로 볼 것이냐 아니면 새로운 충돌의 시작으로 볼 것이냐 하는 관점이다. 후쿠야마의 「역사의 종언」은 미중무역전쟁과 북한 핵문제 등으로 적실성을 상실한 것 같지만 계몽시대 이후 역사철학의 두 기둥인 헤겔과 마르크스, 그리고 코제브의 이론을 깊게 성찰하고 있다는 점에서 쉽게 간과할 글은 아니다. 역사의 종언이라는 관점은 불교와는 맞지 않다고 볼 수 있다. 불교적 관점에서는 인간의 무명에서 나온 욕망이 그치지 않는 한 역사의 투쟁은 끝나지 않으며 역사는 끝나는 것이 아니라 반복된다. 불교에도 말세(末世)가 있지만 그것은 세상의 끝이 아니라 새로운 시작이다. 그러나 후쿠야마에서 종합된 서구의 역사철학이 역사의 동력을 인정을 위한 투쟁과 과학기술의 발전으로 가능해진 욕망의 추구로 본 점은 불교의 역사관을 정립하는데 있어서도 벤치마킹할 수 있는 좋은 관점이라 본다. 불교에서 「인정을 위한 투쟁」은 불교에 풍부한 마음에 관한 이론으로 대체할 수 있다. 이 요구는 플라톤이 인간의 영혼을 이성, 기개(thymos) 그리고 욕망으로 분류한데 기인한다. 그 중 기개가 바로 인정을 위한 요구의 근원이다. 그것은 불교의 탐진치 중 진심(嗔心)이고 아상(我相)의 근원인 제7식에 해당한다. 다음으로 욕망을 충족하기 위한 경제발전은 인간 지혜의 소산인 과학기술의 발전에 의한 것이니 역시 마음의 소산으로 보아도 무방할 것 같다. 여기서 역사를 달려가는 열차에 비유하여 후쿠야마의 이론을 불교적으로 재구성해볼 수 있다. 열차를 움직이는 에너지는 무명에서 기원한 인간의 욕망이고 열차의 진행방향을 결정하는 것은 레일로 볼 수 있다는 것이다. 이런 아이디어의 원천은 베버(Max Weber)이다. 베버에 의하면 인간의 정신과 문화는 기차 레일을 바꿔주는 스위치 맨(오는 열차의 경로를 선택해 주는 사람)과 같이 기차의 진로를 바꿔준다. 그는 역사라는 열차를 움직이는 힘은 인간의 욕망이요 이념은 레일의 진로를 정해 준다. 역사라는 열차는 욕망이라는 에너지로 달리고 인간의 생각으로 이루어진 이념이 설정한 레일 위를 굴러간다는 것이다. 그런데 역사라는 열차를 움직이는 동력이 아무리 강하더라도 레일이 올바른 방향을 향해 있지 않으면 그 열차는 인간 집단을 파멸도 이끌 것이며 그것이 제대로 된 방향으로 향한다면 행복의 세계로 이끌 것이다. 여기서 우리는 모든 것은 오로지 마음이 지어낸 것(一切唯心造)라는 불교의 기본교리와 만나게 된다. 역사를 움직이는 것은 욕망이지만 역사의 방향을 결정하는 것은 인간의 사고, 생각, 이념 등 결국 마음이라는 결론이 도출될 수 있다. 일체유심조라는 말은 내가 마음먹기에 따라서 앞에 놓여있는 바위를 공중으로 부양시킬 수 있다는 그런 이야기라기보다 역사의 동력에 관한 한 인간의 마음이 개인이나 집단, 혹은 인류 전체의 방향을 결정하게 된다는 그런 의미로 이해될 수 있다. 불교에서 역사의 주체는 누구인가? 불교에서 역사는 신이 아니라 인간이 만드는 것이다. 불교의 불국정토는 인공적인 것이다. 아미타불의 극락세계는 법장비구의 48대원에 의하여 이루어졌고 약사여래의 유리광 세계는 보살로 있을 떼 세운 12가지 원으로 건립된 것이다. 이런 세계로 발전하려면 각성된 자의 서원과 이를 함께 원하는 서원들이 모아져야 한다. 끝으로 불교의 역사관은 과거 지향적인가 아니면 미래지향적인가? 계몽시대에서 유래된 진보적 역사관은 비판을 받아왔지만 인류가 진보한다고 보는 관점은 중생이 불성을 깨우쳐 인류사회가 향상되고 발전한다고 보는 불교의 관점과 유사하다고 본다. 소승과 대승에서 공통으로 인정하는 부처인 미륵부처님의 용화세계는 물질적 진보와 정신적 윤리적 진보가 크게 이루어진 세계로 묘사되고 있다. 다른 점은 불국토는 믿는 자 만이 구원을 받는 선택된 세계도 아니고 한 계급이 다른 계급을 타도하고 이루어진 세계가 아니라 「한 중생이라도 지옥고(地獄苦)를 받는 중생이 남아 있으면 성불하지 않겠다는 보살의 큰 서원에 의해 건립된 세계」라는 것이다. 불교는 역사를 「진보의 과학」이라고 하는 정의에 동감할 수 있다. 불교의 중요한 목적이 인간을 깨우쳐 행복한 세상을 만들어 나가는 것이기 때문이다. 그런데 불교에서의 진보는 몇 사람의 지식인들이 모여서 만든 거대 계획에 따라 발전하는 그런 인위적 진보가 아니라 깨달음으로 구습을 타파하고 새로운 습관을 만들어 가는 노력들이 쌓인 문화적 진화의 과정이기도 하다. 불교의 역사관을 정립하는데 있어서 또한 중요한 것은 진실을 등불로 삼아야 한다는 점이다. 인도에서 고대 역사는 진실을 등불로 삼아 개인과 사회를 변혁해 온 불교 세력과 베다의 가르침에만 근거해 이에 대항한 힌두교 세력과의 투쟁의 역사임을 알아야 한다. 불교에서 진실은 역사를 연구하는데 있어서도 기본 가이드라인으로 삼아야 한다. This article is an attempt to establish Buddhist philosophy of history. Does Buddhism have a philosophy of history that distinguishes it from the world major philosophies of history? What is the Buddhist view on history, who is the subject of history, and what are main powers that move history? This article is written to answer these questions. To this end, we examine issues related to "The End of History" written by Francis Fukuyama on the occasion of the end of the Cold War. His work reflect the world major philosophies of history developed since the Enlightenment period. One of the main points of this paper is that we should first presume the existence of historical facts as an important foundation for the study of history. Any research on history should be based on historical facts, so any attempt to deny historical facts or modify or distort past facts from the present point of view should be avoided. The philosophy of history since the Enlightenment period can be divided into the Hegelian philosophy of history based on mental dialectic and the Marxian philosophy of history which changed it into the materialistic dialectic. They both assumed the beginning and the end of history. But Hegel, who saw history as a realization of freedom of mind, claimed that since the French Revolution which adopted ideals of freedom and equality as the universal governing principle of any country, human society has reached the end of history, while Marx claimed that when the proletarian-led communist revolution succeeds and communism comes, history is over. However, in the face of the fall of the Soviet Union and the collapse of socialist bloc, Francis Fukuyama insisted that history had come to an end because of the collapse of communist bloc in the struggle with liberal democracy. He saw the two motive powers that moved history as the struggle for economic development and the struggle for recognition. He wrote that communism could not overcome liberal democracy in the struggle for the economic prosperity and that it could not defeat liberal democracy the champion of universal human rights in the struggle for recognition. Samuel Huntington, however argued that the struggle for ideology in the 20th century would be replaced by the "clash of civilizations". One of the important differences between the two is whether the civilization of science and technology is a universal civilization or only an extension of Western civilization. Another point of view is whether the destruction of communism will be regarded as the end of history or the beginning of a new conflict. Fukuyama's "end of history" seems to have been a mockery in the face of the US-China trade war and the North Korean nuclear issue. But since the theory itself is deeply reflecting the two pillars of philosophy of history Hegel and Marx(and their heir Kozev), it is not easy to overlook. The view that the end of his history is not compatible with Buddhist view of history From a Buddhist point of view, the struggle for history is not over unless the desire from human ignorance is over. History does not come to an end but there will be a new beginning. Buddhism also has its own eschatology, but it is not the end of the world but the new world sprouts there. However, the idea that the forces that move history are the struggle for the pursuit of recognition and the struggle for the pursuit of desire by the development of science and technology is a good point to benchmark in establishing the Buddhist philosophy of history. In his dialogue the Republic, Plato divided the human soul into three parts: reason, courage(thymos), and desire. The request for recognition corresponds to spirit or grit. Buddhism also classified human bad mind into three parts greed, anger(or grit) and desire. In Buddhism, however, instead of reason. there is Buddha nature that can transform every part of human mind into enlightenment. Through enlightenment, the grit becomes quiet, harmonized, not conflict, and desire avoids excess and takes up modest amounts. Economic development to satisfy desires is due to the development of science and technology, which is the product of human wisdom. Here, Fukuyama's theory can be reconstructed in Buddhism by comparing it to a train that runs history. The energy that drives a train is human desire, and it is a rail that can determine the direction of the train. The source of my idea is from Max Weber. Weber emphasized the autonomous influence of ideas, as in his The Protestant Ethic and the Spirit of Capitalism, but unlike Hegel, he did not see the human mind unilaterally determine human behavior. He also did not see that, unlike Marx, material determines human behavior. According to Weber, human spirit and culture change the course of the train like a switchman who changes train rails. "A world view formed by ideologies, like a railroad switchman, determines the course of a train driven by the power of profit." Whether it's an economic struggle to live well or a struggle for recognition, the power to drive a train is human desire, and ideology sets rail's course. The train of history is a train rolling on the rail set by the ideology of human thought with the energy of desire. No matter how strong the power of moving the train is, if the rail is not in the right direction, it will lead to the destruction of the human group. But if it goes in the right direction, it will lead to a world of happiness. Here we meet with one of the basic doctrines of Buddhism, that is, everything that is created by the mind. Force that move history is human desire, but determining the direction of history is human thought, ideology and ultimately human mind. In Buddhism, it is said that everything is made by the mind. But that does not mean that I can lift the rock if I decide to, but it means that the mind will decide direction. it determines the direction of the individual, the group, or the whole of mankind . Who is the subject of history in Buddhism? In Buddhism, history is not made by god but by human mind which reflects the spirit of the Buddha. It is artificial. Amitabha's paradise was made by 48 big wishes of Fazang(法藏) bodhisattva and the glass world of the medicine Buddha was built by the bodhisattva's twelve big wishes. In order to develop into such a world, the vow of the awakened person and the desired vow together are made. Finally, is the Buddhist vie of history either past-oriented or futuristic? The view of progressive history derived from the Enlightenment period may be c